Extreme pressure anti-wear additive, preparation method thereof and application of extreme pressure anti-wear additive in lubricating oil

By combining ceria nanoparticles with ZIF-67 coating, an extreme pressure anti-wear additive was prepared, which solved the stability of the base lubricant under extreme operating conditions and the poor dispersion stability of rare earth nanomaterials, and achieved excellent lubricating performance under high temperature and high load conditions.

CN119752508AActive Publication Date: 2025-04-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411950933.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Under extreme operating conditions such as high temperature and high load, the stability of the base lubricant is poor, resulting in lubrication failure and affecting the operation of the equipment. Rare earth nanomaterials have poor dispersion stability in lubricating oil, which is easy to accumulate, affecting tribological properties. MOFs materials are prone to deform under mechanical action, which may lead to lubrication failure.

Method used

Extreme pressure anti-wear additives were prepared by combining ceria nanoparticles with ZIF-67 cladding. This method adsorbs 2-methylimidazole on the surface of nano ceria through adsorption, and forms ZIF-67 by coordination between cobalt nitrate and 2-methylimidazole, controlling the thickness of the outer ZIF-67 shell to improve dispersion stability.

Benefits of technology

Extreme pressure anti-wear additives show excellent dispersion stability and lubricating properties in lubricating oils, and can maintain lubricating properties under the extreme conditions of high temperature and high load, reducing friction and wear between mechanical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752508A_ABST
    Figure CN119752508A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lubrication, in particular to an extreme pressure anti-wear additive, a preparation method thereof and application of the extreme pressure anti-wear additive in lubricating oil. The invention provides a preparation method of an extreme pressure anti-wear additive, which comprises the following steps: step 1, mixing a cerium dioxide dispersion liquid and a 2-methylimidazole aqueous solution, and sequentially carrying out first stirring and first filtering to obtain first solid powder; 2, mixing the solid powder with a soluble cobalt salt solution, and sequentially carrying out second stirring and second filtering to obtain second solid powder; and repeating the processes of the step 1 and the step 2 on the second solid powder to obtain the extreme pressure anti-wear additive. The extreme pressure anti-wear additive prepared by the preparation method has good dispersion stability in lubricating oil, and can still maintain excellent lubricating performance under extreme pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubrication, and in particular to an extreme pressure anti-wear additive and a preparation method thereof and application thereof in lubricating oil. Background Art

[0002] In industrial production, the existence of friction leads to serious energy loss and component wear, affecting the stable operation of equipment. The introduction of lubricating grease can effectively reduce interface friction and extend the service life of equipment, and is widely used in industrial production. However, under extreme working conditions such as high temperature and high load, the base lubricant fails to lubricate due to poor stability, affecting the operation of the equipment. Nanomaterials have attracted the attention of researchers because of their surface effects, small size effects and quantum size effects, and can effectively improve the tribological properties and stability of lubricants as lubricating additives.

[0003] Rare earth nanomaterials have excellent wear resistance and oxidation resistance, can effectively improve the tribological properties of lubricants, prevent lubricants from failing under extreme working conditions, and are widely used in the field of lubrication. At the same time, due to their special 4f orbitals, rare earth materials are conducive to the occurrence of chemical reactions during friction, thereby forming a friction protection layer at the interface, avoiding direct contact of the interface, and helping to further reduce wear. However, due to their high density, rare earth materials have poor dispersion stability in lubricants and are prone to accumulation during friction, thus affecting tribological properties. Metal organic framework materials (MOFs) are a type of porous crystalline material formed by coordination between metal ions and organic ligands. They have the advantages of highly ordered framework structure, adjustable pore structure, large specific surface area and good chemical stability. They are widely used in gas storage, catalytic reaction, electrochemistry and sensors. In addition, due to the introduction of organic frameworks, compared with inorganic nano-lubricating additives, MOFs materials can show better dispersion stability in lubricants, thereby further improving the tribological properties of lubricants. Zeolitic imidazolate framework MOFs (ZIF) have been widely used in the field of lubricant additives due to their good thermal and chemical stability. However, MOFs materials are prone to deformation under mechanical action, which may lead to lubrication failure under extreme working conditions. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an extreme pressure anti-wear additive and a preparation method thereof and application in lubricating oil. The extreme pressure anti-wear additive prepared by the preparation method has good dispersion stability in lubricating oil and can still maintain excellent lubrication performance under extreme pressure conditions.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an extreme pressure anti-wear additive, comprising the following steps:

[0007] Step 1: mixing a cerium dioxide dispersion and a 2-methylimidazole aqueous solution, and sequentially performing a first stirring and a first filtering to obtain a first solid powder;

[0008] Step 2: mixing the solid powder and the soluble cobalt salt solution, and performing a second stirring and a second filtering in sequence to obtain a second solid powder;

[0009] Repeat the process of step 1 and step 2 with the second solid powder to obtain the extreme pressure and anti-wear additive.

[0010] Preferably, the cerium dioxide dispersion comprises cerium dioxide and water;

[0011] The mass ratio of the cerium dioxide to water is 1:(50-100).

[0012] Preferably, the mass ratio of 2-methylimidazole to water in the 2-methylimidazole aqueous solution is 1:(20-50).

[0013] Preferably, the mass ratio of the soluble cobalt salt to water in the soluble cobalt salt solution is 1:(20-100).

[0014] Preferably, the molar ratio of cerium dioxide in the cerium dioxide dispersion to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:(5-10).

[0015] Preferably, the molar ratio of the soluble cobalt salt in the soluble cobalt salt solution to the 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:(2-10).

[0016] Preferably, the first stirring speed is 300-800 rpm, and the time is 10-30 min;

[0017] The second stirring speed is 300-800 rpm, and the time is 10-30 min;

[0018] The number of repetitions is 3 to 10 times.

[0019] The present invention also provides an extreme pressure and anti-wear additive prepared by the preparation method described in the above technical solution, comprising cerium dioxide nanoparticles and ZIF-67 coated on the surface of the cerium dioxide nanoparticles.

[0020] The present invention also provides the use of the extreme pressure anti-wear additive described in the above technical solution in lubricating oil.

[0021] The present invention also provides a lubricating oil, comprising a base oil and an extreme pressure anti-wear additive;

[0022] The mass percentage of the extreme pressure anti-wear additive in the lubricating oil is 0.1-1%;

[0023] The extreme pressure anti-wear additive is the extreme pressure anti-wear additive described in the above technical solution.

[0024] The invention provides a method for preparing an extreme pressure and anti-wear additive, comprising the following steps: step 1, mixing a cerium dioxide dispersion and a 2-methylimidazole aqueous solution, and sequentially performing a first stirring and a first filtering to obtain a first solid powder; step 2, mixing the solid powder and a soluble cobalt salt solution, and sequentially performing a second stirring and a second filtering to obtain a second solid powder; and repeating the process of step 1 and step 2 on the second solid powder to obtain the extreme pressure and anti-wear additive. The preparation method of the present invention is simple, mainly comprising the following steps: firstly, 2-methylimidazole is adsorbed on the surface of nano-cerium dioxide by adsorption, and then cobalt nitrate is added to form ZIF-67 by coordination of cobalt nitrate and 2-methylimidazole, and the thickness of the outer ZIF-67 shell is controlled by controlling the number of times 2-methylimidazole and cobalt nitrate are added in sequence. At the same time, the prepared extreme pressure anti-wear additive exhibits excellent dispersion stability in base oil: the organic ligand in the MOFs structure is lipophilic, which changes the surface hydrophilicity of nano-cerium dioxide particles, thereby effectively improving the defect of poor dispersion stability of cerium dioxide nanoparticles in lubricating oil; the friction and wear between mechanical components are reduced by the rolling effect, self-repairing effect and friction chemical reaction of the nano-additive (cerium dioxide nanoparticle), and the friction protection layer is generated, and the excellent lubrication performance is still maintained under the extreme conditions of high temperature and high load. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM and TEM images of the extreme pressure and anti-wear additive described in Example 1;

[0026] Figure 2 Schematic diagram of the dispersion stability of the lubricating oil described in Application Example 1;

[0027] Figure 3 is the friction coefficient of the lubricating oil described in Comparative Example 1 and Application Examples 2 to 5;

[0028] Figure 4 is the wear rate of the lubricating oil described in Comparative Example 1 and Application Examples 2 to 5;

[0029] Figure 5 It is a friction coefficient curve diagram of the lubricating oil described in Comparative Example 1 and Application Example 5 under variable load test;

[0030] Figure 6 It is a friction coefficient curve diagram of the lubricating oil described in Comparative Example 1 and Application Example 5 under variable temperature test. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an extreme pressure anti-wear additive, comprising the following steps:

[0032] Step 1: mixing a cerium dioxide dispersion and a 2-methylimidazole aqueous solution, and sequentially performing a first stirring and a first filtering to obtain a first solid powder;

[0033] Step 2: mixing the solid powder and the soluble cobalt salt solution, and performing a second stirring and a second filtering in sequence to obtain a second solid powder;

[0034] Repeat the process of step 1 and step 2 with the second solid powder to obtain the extreme pressure and anti-wear additive.

[0035] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0036] The present invention mixes the cerium dioxide dispersion and the 2-methylimidazole aqueous solution, and sequentially performs a first stirring and a first filtering to obtain a first solid powder.

[0037] In the present invention, the mixing is preferably performed by adding a 2-methylimidazole aqueous solution into the cerium dioxide dispersion.

[0038] In the present invention, the mass ratio of 2-methylimidazole to water in the 2-methylimidazole aqueous solution is preferably 1:(20-50), more preferably 1:(30-40). In the present invention, the water is preferably deionized water. In an embodiment of the present invention, the mass ratio of 2-methylimidazole to water can be 1.15:30.

[0039] In the present invention, the 2-methylimidazole aqueous solution is preferably prepared by mixing 2-methylimidazole and water. The present invention has no special limitation on the mixing process, and the process well known to those skilled in the art can be used.

[0040] In the present invention, the cerium dioxide dispersion preferably comprises cerium dioxide and water, the water is preferably deionized water, and the cerium dioxide is preferably nano cerium dioxide. In the present invention, the particle size of the nano cerium dioxide is preferably 10 to 50 nm, more preferably 20 to 30 nm. In the present invention, the mass ratio of the cerium dioxide to water is preferably 1: (50 to 100), more preferably 1: (60 to 90), and most preferably 1: (70 to 80). In the present invention, the mass ratio of the cerium dioxide to water can be 0.3: 30.

[0041] In the present invention, the cerium dioxide dispersion is preferably prepared by ultrasonically treating cerium dioxide and deionized water. The present invention does not have any special limitation on the ultrasonic process, and the process well known to those skilled in the art can be used.

[0042] In the present invention, the molar ratio of cerium dioxide in the cerium dioxide dispersion to 2-methylimidazole in the 2-methylimidazole aqueous solution is preferably 1:(5-10), more preferably 1:(6-8). In an embodiment of the present invention, the molar ratio of cerium dioxide in the cerium dioxide dispersion to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:8.235.

[0043] The present invention has no special limitation on the method of adding the 2-methylimidazole aqueous solution, and the method may be carried out by a process well known to those skilled in the art.

[0044] In the present invention, the first stirring speed is preferably 300-800 rpm, more preferably 500-600 rpm, the time is preferably 10-30 min, more preferably 15-20 min; the temperature is preferably 20-40° C. In an embodiment of the present invention, the first stirring speed can be 600 rpm, the time can be 15 min, and the temperature can be 25° C.

[0045] In the present invention, the first stirring is used to adsorb 2-methylimidazole on the surface of nano-cerium dioxide by electrostatic adsorption.

[0046] The present invention does not have any special limitation on the first filtering process, and the first filtering process may be performed using a process well known to those skilled in the art.

[0047] After obtaining the first solid powder, the present invention mixes the solid powder with a soluble cobalt salt solution, and sequentially performs a second stirring and a second filtration to obtain a second solid powder.

[0048] In the present invention, the soluble cobalt salt solution preferably includes a soluble cobalt salt and water, the water is preferably deionized water, the soluble cobalt salt is preferably cobalt nitrate hexahydrate and / or cobalt acetate tetrahydrate, more preferably cobalt nitrate hexahydrate; when the soluble cobalt salt is two of the above specific options, the present invention does not have any special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the soluble cobalt salt can be cobalt nitrate hexahydrate.

[0049] In the present invention, the mass ratio of the soluble cobalt salt to water in the soluble cobalt salt solution is preferably 1:(20-100), more preferably 1:(30-80), and most preferably 1:(40-60). In an embodiment of the present invention, the mass ratio of the soluble cobalt salt to water can be 0.62:30.

[0050] In the present invention, the soluble cobalt salt solution is preferably prepared by mixing a soluble cobalt salt and water. The present invention has no special limitation on the mixing process, and the mixing process may be carried out by a process well known to those skilled in the art.

[0051] In the present invention, the mixing is preferably performed by adding a soluble cobalt salt solution to the solid powder. In the present invention, the process of adding the soluble cobalt salt solution is preferably performed under stirring conditions. The present invention does not have any special restrictions on the stirring conditions, and the stirring conditions can be performed under conditions well known to those skilled in the art.

[0052] In the present invention, the molar ratio of 2-methylimidazole in the 2-methylimidazole aqueous solution to the soluble cobalt salt in the soluble cobalt salt solution is preferably 1:(2-5), more preferably 1:(3-4).

[0053] The present invention has no special limitation on the method and process of adding the soluble cobalt salt solution, and the method and process well known to those skilled in the art can be used.

[0054] In the present invention, the second stirring speed is preferably 300-800 rpm, more preferably 500-600 rpm; the time is preferably 10-30 min, more preferably 10-20 min; the temperature is preferably 20-40° C. In an embodiment of the present invention, the second stirring speed can be 600 rpm, the time can be 15 min, and the temperature can be 25° C.

[0055] In the present invention, the number of repetitions is preferably 3 to 10 times, more preferably 4 to 8 times. In an embodiment of the present invention, the number of repetitions can also be 5 times. In the present invention, the purpose of the repetitions is to control the thickness of the ZIF-67 shell.

[0056] After the above-mentioned process of repeating the preparation of the mixed solution and adding the soluble cobalt salt solution for the second stirring is completed, the present invention also preferably includes filtering, washing and drying in sequence. The present invention does not have any special restrictions on the filtering and washing processes, and can be carried out using processes well known to those skilled in the art. In the present invention, the drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 40° C., and the time is preferably 12 hours. In an embodiment of the present invention, the washing can be washing three times with anhydrous ethanol.

[0057] The present invention also provides an extreme pressure and anti-wear additive prepared by the preparation method described in the above technical solution, comprising cerium dioxide nanoparticles and ZIF-67 coated on the surface of the cerium dioxide nanoparticles.

[0058] The present invention also provides the use of the extreme pressure anti-wear additive described in the above technical solution in lubricating oil.

[0059] The present invention also provides a lubricating oil, comprising a base oil and an extreme pressure anti-wear additive;

[0060] The mass percentage of the extreme pressure anti-wear additive in the lubricating oil is 0.1-1%;

[0061] The extreme pressure anti-wear additive is the extreme pressure anti-wear additive described in the above technical solution.

[0062] In the present invention, the base oil preferably includes 500SN, 500N, PAO4, PAO6 or PAO10.

[0063] In the present invention, the mass percentage of the extreme pressure and anti-wear additive in the lubricating oil is 0.1-1%, preferably 0.3-0.8%.

[0064] In the present invention, the method for preparing the lubricating oil preferably comprises the following steps: mixing the base oil and the extreme pressure anti-wear additive, and performing ultrasonic dispersion to obtain the lubricating oil. The present invention does not have any special limitation on the process of ultrasonic dispersion, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the ultrasonic dispersion can be performed for 1 hour at room temperature.

[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] Example 1

[0067] Ultrasonic dispersion of 0.3 g (172, 0.0017 mol) of cerium dioxide nanoparticles in 30 g of deionized water to obtain a cerium dioxide dispersion;

[0068] Dissolve 1.15 g (82, 0.014 mol) of 2-methylimidazole in 30 g of deionized water to obtain a 2-methylimidazole aqueous solution;

[0069] Dissolve 0.62 g (291, 0.0021 mol) of cobalt nitrate hexahydrate in 30 g of deionized water to obtain a cobalt nitrate solution;

[0070] Add the 2-methylimidazole aqueous solution to the cerium dioxide dispersion, stir for 15 minutes (temperature is 25° C., rotation speed is 600 rpm), filter, and obtain a mixed solution;

[0071] The cobalt nitrate solution was added to the mixed solution, stirred for 15 min (temperature was 25° C., rotation speed was 600 rpm), the above process of preparing the mixed solution and adding the cobalt nitrate solution for the second stirring was repeated 5 times, filtered, washed three times with anhydrous ethanol, and vacuum dried at 40° C. for 12 h to obtain an extreme pressure and anti-wear additive (denoted as ZIF-67@CeO2);

[0072] Figure 1 The SEM and TEM images of the extreme pressure and anti-wear additive are shown in Figure 1, wherein (a) is the SEM image and (b) is the TEM image. Figure 1 It can be seen that there is a clear dividing line between ZIF-67 and CeO2 nanoparticles, showing a core-shell structure. The surface of ZIF-67 is very smooth and is coated on the surface of cerium dioxide nanoparticles in the form of nanosheets.

[0073] Application Example 1

[0074] 0.005 g of the extreme pressure and anti-wear additive described in Example 1 was mixed with 4.995 g of 500SN base oil, and ultrasonically dispersed to obtain lubricating oil;

[0075] The lubricating oil is allowed to stand at room temperature for 1 to 4 days, and the absorbance of the dispersion liquid after being allowed to stand for different days is tested by ultraviolet-visible light spectroscopy;

[0076] in Figure 2 is a schematic diagram of the dispersion stability of the lubricating oil, Figure 2 It can be seen that after standing for 96 hours, the relative absorbance of the lubricating oil drops to 0.7, indicating that the extreme pressure and anti-wear additive has relatively excellent dispersion stability.

[0077] Application Example 2

[0078] 9.99 g of 500SN base oil and 0.01 g of the extreme pressure and anti-wear additive described in Example 1 were mixed and ultrasonically dispersed at room temperature for 1 h to obtain lubricating oil (the mass percentage concentration of the extreme pressure and anti-wear additive was 0.1%).

[0079] Application Example 3

[0080] 9.97 g of 500SN base oil and 0.03 g of the extreme pressure and anti-wear additive described in Example 1 were mixed and ultrasonically dispersed at room temperature for 1 hour to obtain lubricating oil (the mass percentage concentration of the extreme pressure and anti-wear additive was 0.3%).

[0081] Application Example 4

[0082] 9.95 g of 500SN base oil and 0.05 g of the extreme pressure and anti-wear additive described in Example 1 were mixed and ultrasonically dispersed at room temperature for 1 hour to obtain lubricating oil (the mass percentage concentration of the extreme pressure and anti-wear additive was 0.5%).

[0083] Application Example 5

[0084] 9.9 g of 500SN base oil and 0.1 g of the extreme pressure anti-wear additive described in Example 1 were mixed and ultrasonically dispersed at room temperature for 1 h to obtain lubricating oil (the mass percentage concentration of the extreme pressure anti-wear additive was 1%).

[0085] Comparative Example 1

[0086] 500SN base oil is used as lubricant.

[0087] Test Case

[0088] The friction performance of the lubricating oils described in Application Examples 2 to 5 was tested under the friction conditions of a load of 150 N, a speed of 0.05 m / s, and a temperature of 40° C.; Figure 3 is the friction coefficient of the lubricating oil described in Comparative Example 1 and Application Examples 2 to 5, Figure 4 is the wear rate of the lubricating oil described in Comparative Example 1 and Application Examples 2 to 5, Figures 3-4 It can be seen that the introduction of extreme pressure and anti-wear additives in different addition ratios can reduce the friction coefficient and wear rate of the 500SN base oil. The average friction coefficient of the 500SN base oil is 0.207. When 0.1wt%, 0.3wt%, 0.5wt% and 1wt% ZIF-67@CeO2 additives are added, the average interface friction coefficients are 0.125, 0.124, 0.127 and 0.121, respectively. When 500SN base oil is used as the lubricating medium, the interface wear volume is 22.344±1.656×10 4 μm 3 As the addition content of the extreme pressure anti-wear additive increases, the interface wear volume gradually decreases. When the addition amount of the extreme pressure anti-wear additive is 0.1wt%, 0.3wt%, 0.5wt% and 1wt%, the interface wear volume is 13.55±1.85×10 4 μm 3 , 7.044±0.352×10 4 μm 3 , 5.43±0.5×10 4 μm 3 and 4.075±0.185×10 4 μm 3 When the additive content is 1wt%, the interface exhibits the most excellent tribological properties, and its friction coefficient is reduced by 41.54% and the wear rate is reduced by 81.76% compared with the 500SN base oil described in Comparative Example 1;

[0089] The friction performance of the lubricating oil described in Application Example 5 was tested under the friction conditions of a speed of 0.05 m / s, a temperature of 40°C, and a load increasing from 50 N to 700 N at a speed of 50 N / 3 min; wherein Figure 5 The friction coefficient curves of the lubricating oils described in Comparative Example 1 and Application Example 5 under variable load tests are shown in FIG. Figure 5 It can be seen that the introduction of 1wt% extreme pressure anti-wear additive can effectively increase the ultimate load of 500SN base oil. When the load rises to 200N, 500SN base oil fails to lubricate. However, after the introduction of the extreme pressure anti-wear additive, the lubricating oil fails at a load of 700N, indicating that the introduction of the extreme pressure anti-wear additive can enable the lubricating oil to maintain lubrication performance under high load.

[0090] The friction performance of the lubricating oil described in Application Example 5 was tested under the friction conditions of a load of 150N, a speed of 0.05m / s, and a temperature increase from 30°C to 130°C at a rate of 10°C / 3min; wherein Figure 6 The friction coefficient curves of the lubricating oils described in Comparative Example 1 and Application Example 5 under variable temperature tests are shown in FIG. Figure 6 It can be seen that the introduction of 1wt% extreme pressure anti-wear additive can effectively improve the stability of 500SN base oil at high temperature and avoid lubrication failure; when the temperature rises to 60°C, 500SN base oil fails to lubricate, but after the introduction of the extreme pressure anti-wear additive, the lubricating oil can still maintain a stable lubrication effect at 130°C, indicating that the introduction of the extreme pressure anti-wear additive can enable the lubricating oil to maintain lubrication performance at high temperatures.

[0091] In summary, the extreme pressure anti-wear additive of the present invention exhibits excellent lubrication performance and is particularly suitable for lubrication under extreme conditions of high temperature and high load.

[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an extreme pressure and anti-wear additive, characterized in that: The following steps are involved: Step 1: mixing a cerium dioxide dispersion and a 2-methylimidazole aqueous solution, and sequentially performing a first stirring and a first filtering to obtain a first solid powder; Step 2: mixing the solid powder and the soluble cobalt salt solution, and performing a second stirring and a second filtering in sequence to obtain a second solid powder; Repeat the process of step 1 and step 2 with the second solid powder to obtain the extreme pressure and anti-wear additive.

2. The preparation method according to claim 1, characterized in that The cerium dioxide dispersion comprises cerium dioxide and water; The mass ratio of the cerium dioxide to water is 1:(50-100).

3. The preparation method according to claim 1, characterized in that: The mass ratio of 2-methylimidazole to water in the 2-methylimidazole aqueous solution is 1:(20-50).

4. The preparation method according to claim 1, characterized in that: The mass ratio of the soluble cobalt salt to water in the soluble cobalt salt solution is 1:(20-100).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of cerium dioxide in the cerium dioxide dispersion to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:(5-10).

6. The preparation method according to claim 5, characterized in that: The molar ratio of the soluble cobalt salt in the soluble cobalt salt solution to the 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:(2-10).

7. The preparation method according to claim 1, characterized in that: The first stirring speed is 300-800 rpm, and the time is 10-30 min; The second stirring speed is 300-800 rpm, and the time is 10-30 min; The number of repetitions is 3 to 10 times.

8. The extreme pressure and anti-wear additive prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises cerium dioxide nanoparticles and ZIF-67 coated on the surface of the cerium dioxide nanoparticles.

9. Use of the extreme pressure anti-wear additive according to claim 8 in lubricating oil.

10. A lubricating oil, characterized in that: Includes base oil and extreme pressure and anti-wear additives; The mass percentage of the extreme pressure anti-wear additive in the lubricating oil is 0.1-1%; The extreme pressure anti-wear additive is the extreme pressure anti-wear additive according to claim 8.

Citation Information

Patent Citations

  • Silicon-coating cerium oxide nano-powder material as well as preparation method and application thereof

    CN101875873A

  • Process for synthesis of ce3+, EU2+ co-doped basif6 phosphor

    IN201921035528A

  • Nickel-coated hexagonal boron nitride nanosheet composite powder, preparation therefor, and high-performance composite ceramic cutter material

    WO2020155737A1